2018
DOI: 10.1021/acsnano.8b02365
|View full text |Cite
|
Sign up to set email alerts
|

Modified Magnesium Hydroxide Nanoparticles Inhibit the Inflammatory Response to Biodegradable Poly(lactide-co-glycolide) Implants

Abstract: Biodegradable polymers have been extensively used in biomedical applications, ranging from regenerative medicine to medical devices. However, the acidic byproducts resulting from degradation can generate vigorous inflammatory reactions, often leading to clinical failure. We present an approach to prevent acid-induced inflammatory responses associated with biodegradable polymers, here poly(lactide- co-glycolide), by using oligo(lactide)-grafted magnesium hydroxide (Mg(OH)) nanoparticles, which neutralize the ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
53
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 78 publications
(53 citation statements)
references
References 33 publications
0
53
0
Order By: Relevance
“…New drug-eluting stents have been developed to not only minimize neointimal hyperplasia and reduce restenosis after revascularization, but also minimize stent thrombosis, a problem that was observed at higher frequency with the first generation stents [114]. Recently, Lih et al developed a new approach to prevent acid-induced inflammatory responses associated with biodegradable PLGA, by neutralizing the acidic environment using oligo(lactide)-grafted magnesium hydroxide (Mg(OH) 2 ) nanoparticles [115]. They demonstrated in porcine models that incorporating the modified Mg(OH) 2 nanoparticles within degradable coatings on drug-eluting arterial stents could efficiently attenuate the inflammatory response and in-stent intimal thickening [115].…”
Section: Implantable Device With Biodegradable Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…New drug-eluting stents have been developed to not only minimize neointimal hyperplasia and reduce restenosis after revascularization, but also minimize stent thrombosis, a problem that was observed at higher frequency with the first generation stents [114]. Recently, Lih et al developed a new approach to prevent acid-induced inflammatory responses associated with biodegradable PLGA, by neutralizing the acidic environment using oligo(lactide)-grafted magnesium hydroxide (Mg(OH) 2 ) nanoparticles [115]. They demonstrated in porcine models that incorporating the modified Mg(OH) 2 nanoparticles within degradable coatings on drug-eluting arterial stents could efficiently attenuate the inflammatory response and in-stent intimal thickening [115].…”
Section: Implantable Device With Biodegradable Materialsmentioning
confidence: 99%
“…Recently, Lih et al developed a new approach to prevent acid-induced inflammatory responses associated with biodegradable PLGA, by neutralizing the acidic environment using oligo(lactide)-grafted magnesium hydroxide (Mg(OH) 2 ) nanoparticles [115]. They demonstrated in porcine models that incorporating the modified Mg(OH) 2 nanoparticles within degradable coatings on drug-eluting arterial stents could efficiently attenuate the inflammatory response and in-stent intimal thickening [115]. Their results suggested that modifications of biodegradable nanoparticles could be useful to broaden the applicability and improve clinical success of biodegradable devices used in various biomedical fields.…”
Section: Implantable Device With Biodegradable Materialsmentioning
confidence: 99%
“…To overcome this, basic additives such as Mg(OH) 2 and Ca(OH) 2 are encapsulated in the PLGA matrix. [65,66] Besides PLGA, significant efforts are being made in the direction of developing degradable microgels based on other polymers in order to facilitate the drug release along with the renal clearance of the final degraded products, leading to reduced toxicity. To explore the potential of microgel particles for biomedical applications, a number of different strategies have been introduced in the chemical design of microgels such as hydrazone-, ketal-, acetal-, disulfide-, carbonate ester-, and siloxane-based crosslinking which can be cleaved by tuning the surrounding medium.…”
Section: Degradable Crosslinking For Microgelsmentioning
confidence: 99%
“… 31 , 32 Based on the finding from our previous studies, in this study, we designed a PLGA/MH composite scaffold with pH neutralization and anti-inflammatory properties on the implanting site. 7 , 19 , 32 36 Additionally, in order to enhance osteogenic activity, the PLGA/MH composite scaffold surface was coated with polydopamine (PDA) as an adhesive interlayer and BMP2 was sequentially immobilized on the PDA-coated PLGA/MH composite scaffold. After configuring the scaffold, we evaluated in vitro and in vivo osteogenic activity of the BMP2-immobilized PLGA/MH scaffold.…”
Section: Introductionmentioning
confidence: 99%